Peran Guru Dan Kepala Sekolah Dalam Implementasi Kurikulum Merdeka Belajar - Reisya Diva Maharani Putri; Tannia Alfianti Putri; Asih Andriyati Mardliyah; Sefira Amelia Rosadha; Aditya Nata Widigda (Politeknik Kampar, 2024)
Culrricullum changes are part of improving the education systelm in Indonesia. This study outlines the role of the principal in implementing the independent curricullum at SD Islam Al Azhar. This study was conducted to investigate thel professionalism of school principals in implementing the independent curricullum. This type of research is descriptive qualitative using phenomenological analysis. Data were collected by interviewing school principals, curricullum representatives, and independent curricullum implementing teachers. The results showld that the implementation of the independent curricullum madel teachers more professional through various kinds of coaching and training. Principals carry out their roles as mediators and motivators for teacher participation in curricullum training. The principal also acts as a participant in regullar meetings or discussions. The principal is also a supervisor and evaluator in the implementation of the independent curricullum. The factor faced by the principal is the lack of smooth internet neltwork as a means for teachers to use technology in learning smoothy. The expected results of the theories in the research are taken into consideration by school principals to make decisions in answering problems and improving the qulality or qulality of eldulcation through the implementation of an independent curricullum.